Role of Glycation in Type 2 Diabetes Mellitus and Its Prevention through Nymphaea Species. (27th October 2021) - Ishrat, Nayab; Khan, Hamda; Patel, Om P. S.; Mahdi, Abbas Ali; Mujeeb, Farina; Ahmad, Saheem
Abstract : The dysregulation of glucose metabolism that includes the modification of biomolecules with the help of glycation reaction results in the formation of advanced glycation end products (AGEs). The formation of AGEs may activate receptors for advanced glycation end products which induce intracellular signaling, ultimately enhancing oxidative stress, a well-known contributor to type 2 diabetes mellitus. In addition, AGEs are possible therapeutic targets for the treatment of type 2 diabetes mellitus and its complications. This review article highlights the antioxidant, anti-inflammatory, and antidiabetic properties of the Nymphaea species, and the screening of such aquatic plants for antiglycation activity may provide a safer alternative to the adverse effects related to glucotoxicity. Since oxidation and glycation are relatively similar to each other, therefore, there is a possibility that the Nymphaea species may also have antiglycating properties because of its powerful antioxidant properties. Herbal products and their derivatives are the preeminent resources showing prominent medicinal properties for most of the chronic diseases including type 2 diabetes mellitus. Among these, the Nymphaea species has also shown elevated activity in scavenging free radicals. This species has a load of phytochemical constituents which shows various therapeutic and nutritional value including anti-inflammatory and antioxidant profiles. To the best of our knowledge, this is the first article highlighting the possibility of an antiglycation value of the Nymphaea species by inhibiting AGEs in mediation of type 2 diabetes mellitus. We hope that in the next few years, the clinical and therapeutic potential may be explored and highlight a better perspective on the Nymphaea species in the inhibition of AGEs and its associated diseases such as type 2 diabetes mellitus.